Social Protectionism, Transfered Mothering, and the Struggle for Reproductive Health - Suely Gomes Costa (Revista Estudos Feministas, 2002)
This article analyses the nature of the tensions brought about by the entrance of women into public space and the rise of protectionist systems in Brazil. It places both experience and theory in the long-range context of women’s history, gender relations and feminist movements. Feminist struggles and domesticity patterns reaffirm the home as the place par excellence of protectionist practices, something that prevented or delayed the advent of public protectionist systems. The different relationships among those women who remained at home and those that managed to develop their activities outside the domestic environment will certainly establish inequalities as to the obtention of social rights. The article examines evidence of change in the historical trend in the struggle for universal reproductive rights during the 1980s.